New directions in colour studies - Biggam, C. P. (Carole Patricia), 1946- (John Benjamins Pub. Co., 2011)
Colour studies attracts an increasingly wide range of scholars from across the academic world. Contributions to the present volume offer a broad perspective on the field, ranging from studies of individual languages through papers on art, architecture and heraldry to psychological examinations of aspects of colour categorization, perception and preference. The chapters have been developed from papers and posters presented at a conference on Progress in Colour Studies (PICS08) held at the University of Glasgow. The volume both updates research reported at the earlier PICS04 conference (publishe.